teori administrasi dan metodologi administrasi publik - Jurnal Governance Jurnal Kebijakan & Manajemen Publik; Mas Roro Lilik Ekowanti (Governance, JKMP (Governance, Jurnal Kebijakan & Manajemen Publik), 2010)
In the context of an ontology of administrative science that is under stood by four key administrative, organizational, administrative principles, administrator. The essence of the philosophy of administration is a trust and responsibility. The value of trust and responsibility in the future be important for the development of administrative science in addition to the effective-ness, efficiency, rationality and fairness. While the context of epistemology, the study of public administration because the number was not less important to follow three methodologies: (1). Lack of testing the theory; (2). The lack of cumulative research, because of low initial study and the low effort to build theory through the early work; (3). Publication of research is rarely done. Methodological limitations associated with restriction and development of administrative theory in epistemology. The choice of strategy of both qualitative and quantitative research relevant to the development of contemporary public administration theory. A variety of public problems and issues of public administration provide a space for the use of methods in public administration, the choice of using the combination method in the future become a rational choice in order to obtain validity and reliability in finding generalizations as well asthe depth of analysis in order to obtain the conclusion of representation. With the methodology of public administration that are easier to be under stood by scientists administration is expected to produce development of administrative science theory of the state administration which is conducive for developing countries especially Indonesia.